Contribution of bioremediation to solve pollution problems and its relationship with sustainable development - Garzón, Jennyfer M.; Rodríguez Miranda, Juan Pablo; Hernández Gómez, Catalina (Universidad y Salud, 2017)
Introduction: Bioremediation is an alternative to traditional physico-chemical techniques for the remediation of compounds that pollute the environment. Objective: To review the application of bioremediation and its contribution to the fulfillment of one of the objectives of sustainable development. Materials and methods: A descriptive study was made by means of documentary review about the possibilities and limitations of biotechnology in the treatment of problems of contamination. Results: Among the main technologies that have been registered since the decade of 1970, bioremediation has proven to be profitable and efficient in the removal of certain pollutants. Conclusions: Despite the benefits of bioremediation technologies, there are some difficulties in the application due to the restrictions imposed by the substrate and environmental variability, the limited potential of biodegradation and the viability of microorganisms of natural origin, among others.